Can data assetization drive high-quality enterprise development?—Evidence from China’s “Specialized, refined, unique, and innovative” SMEs - Lin Li; Jiulin Zhu (PLoS ONE, 2025)
Data assetization empowers the high-quality development of “Specialized, Refined, Distinctive, and Innovative” (SRDI) small and medium-sized enterprises (SMEs) by enhancing organizational performance and driving innovation. Based on this, this study selects SRDI SMEs in China from 2013 to 2023 as samples. It constructs a keyword graph spectrum based on enterprise annual report texts to quantitatively assess the level of data assetization and investigates whether data assetization can facilitate the high-quality development of these SMEs. The research findings indicate that: (1) data assetization significantly contributes to the high-quality development of SRDI SMEs, primarily through two mechanisms—enhancing strategic differentiation and improving resource allocation efficiency; (2) the robustness of these findings is confirmed through a series of tests, including alternative specifications of dependent variables, inclusion of additional control variables, subsample analyses, and the exclusion of potential confounding factors; (3) further analysis grounded in the TOE (Technology–Organization–Environment) framework demonstrates that the positive impact of data assetization is amplified by firm-level innovation capacity, customer relationship strength, regional characteristics, and the extent of enterprise digital finance development. This study contributes to advancing the understanding of how data assetization influences the high-quality development of SRDI SMEs, offering a theoretical foundation for future research in this domain.